PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEJABAT LELANG DI LINGKUNGAN KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG PALU - Damin, Buang Mohamad (Katalogis, 2018)
This study aims to uncover simultaneous influence of motivation and competency on the performance of auction officials in The Assest and Auction Service Office of Palu by using explanative pettern to show the relationships of variabels studied. Population consists of 50 auction users from government and non-government agencies. The result shows that competency and motivation ssimultaneously have significant influence on the performance of auction officers in The Office of Assets and Auction Service in Palu of 0.618. it means that the influence of independent variables on the dependent variable is strong. While adjested R square or determinant cofficient (R2) that indicates partial influence between competency and motivation on the performance of auction officers is 0.356 or 35.6%. This means that independent variables have influence on the dependent variable of 35.6% while the reamining 64.4% is influenced by other variables that are not studied.